Demand for off-grid solar electricity: Experimental evidence from Rwanda - Michael Grimm; Luciane Lenz; Jörg Peters; Maximiliane Sievert (University of Bonn, Center for Development Research (ZEF), 2017)
Providing electricity to the unconnected 1.1 billion people in developing countries is one of the top political priorities of the international community, yet the costs of reaching this objective are very high. The present paper examines whether the objective and the associated costs are justified by the value that target beneficiaries assign to electricity. We provide experimental evidence on the revealed willingness-to-pay (WTP) for three types of off-grid solar electricity devices. Our findings show that households are willing to dedicate a substantial part of their expenditures to electricity. In absolute terms, though, the WTP does not suffice to reach cost-covering prices. Different payment schemes, which we randomized across our sample, do not alter the WTP significantly. If universal electricity access is to be achieved, direct subsidies might be necessary. We argue that from a public policy perspective it is more rationale to promote off-grid solar than grid-based electrification because of its better cost-benefit performance.
Keywords: D12; O12; O13; Q28; Q41; 330; technology adoption; electrification; willingness-to-pay; real-purchase offer game; energy access